Potential lipid-lowering effects of preussin B on inhibition of intestinal cholesterol absorption: integrative mechanisms of action and proteomic analysis - Ontawong, Atcharaporn; Inchai, Jakkapong; Holasut, Pannita; Chiangjong, Wararat; Chieochansin, Thaweesak; Crucitti, Davide; Orgueira, Adrián Mosquera; Rojanaverawong, Worarat; Saithong, Thanthakan; Tunkaew, Kornwalai; Wiriyawaree, Hongsiree; Thongpat, Kittisak; et al. (Frontiers in Pharmacology, 2025)
IntroductionHyperlipidemia remains a significant risk factor for cardiovascular diseases and is a leading cause of death, driving the need for novel and effective cholesterol-lowering agents. Preussin (1) has recently demonstrated lipid-lowering effects by inhibiting intestinal cholesterol absorption in human colorectal adenocarcinoma (Caco-2) cells and in an ex vivo intestinal loop in rats, comparable to those of ezetimibe. Ezetimibe is the only drug that targets reducing intestinal cholesterol absorption. Recently, two natural (preussin C, 2, and preussin B, 4) and three unnatural (3, 5, and 6) analogues of preussin have been synthesized and also displayed interesting lipid-lowering effects in human hepatocellular carcinoma (HepG2) cells. However, the underlying mechanisms and the potential lipid-lowering effects of preussin and its synthetic analogues in inhibiting cholesterol absorption are not yet fully understood.MethodsThis study aims to evaluate the inhibitory effect of cholesterol absorption by preussin and its analogues using a fluorescent-micelle cholesterol transport in intestinal Caco-2 cells, which further confirmed by an in vivo cholesterol absorption assay. The most potent analogue was further investigated for its cellular and molecular mechanisms in reducing lipid levels and identifying possible target proteins.ResultsAll synthetic derivatives markedly inhibited cholesterol absorption in the intestinal Caco-2 cells to a similar extent as preussin and ezetimibe. However, only compound 4 (preussin B) displayed the most significant reduction in plasma cholesterol, identical to preussin and ezetimibe, with similar potency in rats. The precise mechanisms and potential targets of this potent compound were additionally identified using protein binding assay and label-free quantification via proteomics analysis. The results revealed substantial differential expression in four proteins associated with lipid metabolism. Notably, glutamic-oxaloacetic transaminase 2 (GOT2), one of the altered proteins, was shown to interact with compound 4 in a protein binding assay. Molecular dynamics simulation analysis indicated that compound 4 binds to a pocket on GOT2 comparable to that of its natural cofactor. This interaction, combined with the observed downregulation of GOT2 expression, contributed to the inhibition of cholesterol absorption.ConclusionThese findings suggest that synthetic compound 4 (preussin B) is a promising candidate for inhibiting cholesterol absorption in the treatment of hyperlipidemia.